Porous graphene reinforced aluminum-based composite material and preparation method thereof

By using porous graphene as the reinforced phase in aluminum-based composite materials, and using predispersed ball milling, high-speed ball milling, discharge plasma sintering and hot extrusion processes, the problem of hard and brittle phase reaction between graphene and aluminum-based composite materials is solved, and the mechanical properties of the composite materials are significantly improved.

CN119839291APending Publication Date: 2025-04-18KUNMING UNIV OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510039310.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In graphene-reinforced aluminum-based composite materials, Al is more likely to react interfacially with graphene, producing a hard and brittle phase Al4C3, thereby weakening the reinforcement effect of the enhanced phase and resulting in insufficient mechanical properties of the material.

Method used

Porous graphene is used as the reinforced phase to be combined with aluminum-based material. Through pre-dispersed ball milling, high-speed ball milling, discharge plasma sintering and hot extrusion, interface combination is optimized, crack propagation is reduced, and external stress is absorbed and dispersed through the three-dimensional network structure.

Benefits of technology

It significantly improves the strength and fatigue resistance of the composite material, reduces the negative impact of the hard and brittle phase Al4C3 on the material, and improves the comprehensive mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119839291A_ABST
    Figure CN119839291A_ABST
Patent Text Reader

Abstract

The invention discloses a porous graphene reinforced aluminum-based composite material and a preparation method thereof, and belongs to the technical field of metal-based composite material preparation. The preparation method comprises the following steps: (1) pre-dispersing and ball-milling; (2) ball milling treatment; (3) sintering and molding; and (4) carrying out hot extrusion on the sintered block obtained in the step (3), and cooling to obtain the porous graphene reinforced aluminum-based composite material. According to the porous graphene reinforced aluminum-based composite material prepared through the preparation method, more contact points can be provided, interface bonding can be enhanced, crack propagation can be reduced, the strength of the composite material can be remarkably improved, meanwhile, negative effects caused by hard and brittle phases on the composite material can be effectively weakened, and therefore the comprehensive mechanical property of the composite material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal-based composite material preparation, and relates to a porous graphene-reinforced aluminum-based composite material and a preparation method thereof. Background Art

[0002] Aluminum alloys and aluminum-based composites have the characteristics of light weight, easy ductility, good electrical and thermal conductivity, and are widely used in automobile manufacturing, aerospace, electrical and electronic fields. However, the mechanical properties of aluminum alloys and aluminum-based composites are poor, which limits their application to a certain extent. Graphene, as a new type of nano two-dimensional material, has the characteristics of high conductivity, high elastic modulus and low thermal expansion coefficient, and is widely used in the manufacturing fields of electronic devices, flexible materials and films. In addition, graphene also has properties such as high specific surface area, high ductility and high tensile strength. Compared with ceramic materials, graphene, as a reinforcing phase of the aluminum matrix, can improve the toughness and conductivity of aluminum alloys and achieve lightweight.

[0003] At present, the research on graphene-enhanced aluminum-based composites mainly focuses on the exploration and optimization of preparation processes and the improvement of mechanical properties. For graphene-enhanced aluminum-based composites, the uniformity of the dispersion of graphene as a reinforcement phase in the matrix material and the degree of interface bonding between the graphene reinforcement phase and the aluminum-based matrix material are important factors affecting the reinforcement effect of the reinforcement phase. However, in graphene-enhanced aluminum-based composites, Al is more likely to react with graphene at the interface to produce a hard and brittle phase Al4C3, thereby weakening the strengthening effect of the reinforcement phase. Therefore, the uneven dispersion of graphene and harmful interface reactions have become key factors restricting the development of graphene-enhanced aluminum-based composites.

[0004] Therefore, it is necessary to provide a porous graphene-reinforced aluminum-based composite material and a preparation method thereof, so that the graphene reinforcement phase is evenly dispersed, while weakening the negative impact of the hard and brittle phase Al4C3 on the composite material, significantly improving the strength of the composite material, so that the graphene reinforcement phase can more fully exert the strengthening effect and improve the comprehensive mechanical properties of the composite material. Summary of the invention

[0005] In order to overcome the problems in the background technology, the present invention obtains a composite material by using porous graphene as a reinforcing phase and compounding it with an aluminum-based material. The porous graphene reacts with the aluminum matrix to provide more contact points and optimize interface bonding. At the same time, the three-dimensional network structure of the porous graphene can absorb and disperse external stress, which helps to improve the toughness of the composite material, reduce crack propagation, and enhance the material's fatigue resistance, thereby improving the comprehensive mechanical properties of the composite material. By combining a specific preparation method, the material preparation temperature is significantly reduced, the carbon-aluminum interface reaction is reduced, the carbon-aluminum interface bonding stability is improved, and the uniform dispersion of the porous graphene in the aluminum matrix is ​​achieved, thereby further improving the comprehensive mechanical properties of the composite material.

[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0007] In one aspect, the present invention provides a method for preparing a porous graphene reinforced aluminum-based composite material, the preparation method comprising the following steps:

[0008] (1) Pre-dispersion ball milling: Under argon protection, the mixed powder of porous graphene powder and Al powder is pre-dispersed by ball milling to achieve pre-dispersion of porous graphene.

[0009] (2) ball milling: under argon protection, the mixed powder after pre-dispersion and ball milling in step (1) is subjected to high-speed ball milling to achieve cold welding and obtain cold welding powder;

[0010] (3) Sintering: spark plasma sintering the cold welding powder obtained in step (2) to obtain a sintered block;

[0011] (4) hot extruding the sintered block obtained in step (3), and obtaining a porous graphene-reinforced aluminum-based composite material after cooling.

[0012] Preferably, in step (1), the mass of the porous graphene powder accounts for 0.2% to 1% of the total mass of the mixed powder, and the remainder is Al powder.

[0013] Preferably, in step (1), the ball-to-material ratio is 20:1, the ball milling speed is 200 rpm, and the ball milling time is 6 to 8 hours.

[0014] Preferably, in step (1), 0.4% of stearic acid by weight of the total weight of the mixed powder is added as a processing control agent during ball milling.

[0015] Preferably, in step (2), the ball-to-material ratio is 20:1, the ball milling speed is 450 rpm, and the ball milling time is 30 to 60 min.

[0016] Preferably, in step (3), the sintering vacuum degree is less than 10 Pa, the sintering temperature is 450° C. to 550° C., the temperature is kept at 20 min, and the sintering pressure is 30 to 50 MPa.

[0017] Preferably, in step (4), the extrusion temperature is 550° C. and the extrusion ratio is 9:1 to 25:1.

[0018] Another aspect of the present invention provides a porous graphene reinforced aluminum-based composite material, which is prepared by the above-mentioned preparation method.

[0019] Beneficial effects of the present invention:

[0020] 1. The present invention adopts porous graphene as a reinforcing phase, which can provide more contact points and enhance interface bonding. At the same time, the three-dimensional network structure of porous graphene is used to absorb and disperse external stress, weaken the negative impact of the hard and brittle phase Al4C3 on the composite material, and improve the comprehensive mechanical properties of the composite material.

[0021] 2. Compared with the traditional casting method, the preparation method of the present invention is not limited in the volume fraction of the reinforcing phase added, the composition can be flexibly adjusted, the risk can be reduced, and the shortcomings of grain boundary segregation and uneven distribution of the reinforcing phase can be effectively overcome. The prepared composite material has controllable grain refinement and uniform microstructure.

[0022] 3. The present invention adopts a spark plasma sintering process to prepare the composite material, which can perform sintering at a temperature lower than the melting point of the composite material and has lower energy consumption than the traditional melting and casting process.

[0023] 4. The present invention adopts hot extrusion processing technology to prepare the composite material. A higher extrusion ratio can further improve the density of the composite material and refine the grains, so that the prepared composite material has better comprehensive performance.

[0024] 5. The room temperature tensile strength of the porous graphene reinforced aluminum-based composite material prepared by the present invention reaches 425.45 MPa, and the elongation can reach 18.25%.

[0025] 6. The porous graphene reinforced aluminum-based composite material prepared by the present invention has the advantages of high specific strength and specific stiffness, excellent electrical and thermal conductivity, good corrosion resistance and wear resistance, and low density.

[0026] 7. In the process of ball milling, the present invention adds stearic acid as a processing control agent to prevent large-area cold welding during the ball milling process, improve dispersibility, control particle size, and thus improve the performance and processing effect of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scan of the microstructure of Al powder of the present invention;

[0028] Figure 2 This is a scanned image of the porous graphene microstructure of the present invention;

[0029] Figure 3 This is a scan of the microstructure of reduced graphene oxide in the comparative example of the present invention;

[0030] Figure 4 The room temperature tensile mechanical property curves of Example 2 of the present invention and Comparative Examples 1 and 2 are shown. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the described contents.

[0032] In the examples and comparative examples of the present invention, chemical reagents not specifically described were commercially available analytically pure reagents for the experiments.

[0033] Example 1

[0034] (1) Weigh 29.94 g of pure aluminum powder (such as Figure 1 As shown), 0.06g porous graphene powder (as Figure 2 As shown in the figure, 0.12g of stearic acid (used as a process control agent to prevent large-area cold welding during ball milling) was placed in a stainless steel ball milling jar and filled with argon. Under the condition of a ball-to-material ratio of 20:1, a planetary ball mill was used to firstly mill at 200 rpm for 6 hours to pre-disperse the porous graphene.

[0035] (2) After the ball milling in step (1) is completed, high-speed ball milling is continued for 30 minutes at a ball milling speed of 450 rpm to achieve cold welding.

[0036] (3) The ball-milled mixed powder was taken out from a vacuum glove box, and then spark plasma sintering was performed using a graphite mold at a sintering temperature of 500°C, a sintering pressure of 50 MPa, and a holding time of 20 min to obtain a porous graphene-reinforced aluminum-based composite material sample with a diameter of 30 mm and a thickness of about 20 mm.

[0037] (4) After the surface of the sintered aluminum-based composite material is polished smooth with sandpaper, hot extrusion is performed at 550° C. with an extrusion ratio of 9:1 to obtain a round rod-shaped aluminum material with a diameter of 10 mm, namely, a porous graphene-reinforced aluminum-based composite material.

[0038] The porous graphene reinforced aluminum-based composite material prepared in this example was processed by wire cutting into a sample that can be used for stretching, and a tensile test was carried out to test its room temperature tensile properties. The mechanical property results are shown in Table 1.

[0039] Example 2

[0040] (1) Weigh 29.88 g pure aluminum powder, 0.12 g porous graphene powder, and 0.12 g stearic acid (used as a process control agent to prevent large-area cold welding during ball milling) and place them in a stainless steel ball milling jar, which is filled with argon. At a ball-to-material ratio of 20:1, a planetary ball mill is used to pre-disperse the porous graphene at 200 rpm for 8 hours.

[0041] (2) After the ball milling in step (1) is completed, high-speed ball milling is continued for 30 minutes at a ball milling speed of 450 rpm to achieve cold welding.

[0042] (3) The ball-milled mixed powder was taken out from a vacuum glove box, and then spark plasma sintering was performed using a graphite mold at a sintering temperature of 550°C, a sintering pressure of 50 MPa, and a holding time of 20 min to obtain a porous graphene-reinforced aluminum-based composite material sample with a diameter of 30 mm and a thickness of about 20 mm.

[0043] (4) After the surface of the sintered aluminum-based composite material is polished smooth with sandpaper, hot extrusion is performed at 550° C. with an extrusion ratio of 25:1 to obtain a round rod-shaped aluminum material with a diameter of 6 mm, namely, a porous graphene-reinforced aluminum-based composite material.

[0044] The porous graphene reinforced aluminum-based composite material prepared in this example was processed into a sample that can be stretched by wire cutting, and a tensile test was performed to test its room temperature tensile properties. The results are as follows: Figure 4 The mechanical properties are shown in Table 1.

[0045] Example 3

[0046] (1) Weigh 29.82 g of pure aluminum powder, 0.18 g of porous graphene powder, and 0.12 g of stearic acid (used as a process control agent to prevent large-area cold welding during ball milling) and place them in a stainless steel ball milling jar, which is then filled with argon. At a ball-to-material ratio of 20:1, a planetary ball mill is used to pre-disperse the porous graphene at 200 rpm for 7 hours.

[0047] (2) After the ball milling in step (1) is completed, high-speed ball milling is continued for 50 minutes at a ball milling speed of 450 rpm to achieve cold welding.

[0048] (3) The ball-milled mixed powder was taken out from a vacuum glove box, and then spark plasma sintering was performed using a graphite mold at a sintering temperature of 450°C, a sintering pressure of 50 MPa, and a holding time of 20 min to obtain a porous graphene-reinforced aluminum-based composite material sample with a diameter of 30 mm and a thickness of about 20 mm.

[0049] (4) After the surface of the sintered aluminum-based composite material is polished smooth with sandpaper, hot extrusion is performed at 550° C. with an extrusion ratio of 25:1 to obtain a round rod-shaped aluminum material with a diameter of 6 mm, namely, a porous graphene-reinforced aluminum-based composite material.

[0050] The porous graphene reinforced aluminum-based composite material prepared in this example was processed by wire cutting into a sample that can be used for stretching, and a tensile test was carried out to test its room temperature tensile properties. The mechanical properties are shown in Table 1.

[0051] Example 4

[0052] (1) Weigh 29.76 g pure aluminum powder, 0.24 g porous graphene powder, and 0.12 g stearic acid (used as a process control agent to prevent large-area cold welding during ball milling) and place them in a stainless steel ball milling jar, which is then filled with argon. At a ball-to-material ratio of 20:1, a planetary ball mill is used to pre-disperse the porous graphene at 200 rpm for 8 hours.

[0053] (2) After the ball milling in step (1) is completed, high-speed ball milling is continued for 60 minutes at a ball milling speed of 450 rpm to achieve cold welding.

[0054] (3) The ball-milled mixed powder was taken out from a vacuum glove box, and then spark plasma sintering was performed using a graphite mold at a sintering temperature of 550°C, a sintering pressure of 40 MPa, and a holding time of 20 min to obtain a porous graphene-reinforced aluminum-based composite material sample with a diameter of 30 mm and a thickness of about 20 mm.

[0055] (4) After the surface of the sintered aluminum-based composite material is polished smooth with sandpaper, hot extrusion is performed at 550° C. with an extrusion ratio of 14:1 to obtain a round rod-shaped aluminum material with a diameter of 8 mm, namely, a porous graphene-reinforced aluminum-based composite material.

[0056] The porous graphene reinforced aluminum-based composite material prepared in this example was processed by wire cutting into a sample that can be used for stretching, and a tensile test was carried out to test its room temperature tensile properties. The mechanical properties are shown in Table 1.

[0057] Example 5

[0058] (1) Weigh 29.70 g of pure aluminum powder, 0.30 g of porous graphene powder, and 0.12 g of stearic acid (used as a process control agent to prevent large-area cold welding during ball milling) and place them in a stainless steel ball milling jar, which is then filled with argon. At a ball-to-material ratio of 20:1, a planetary ball mill is used to mill at 200 rpm for 7 hours to pre-disperse the porous graphene.

[0059] (2) After the ball milling in step (1) is completed, high-speed ball milling is continued for 40 minutes at a ball milling speed of 450 rpm to achieve cold welding.

[0060] (3) The ball-milled mixed powder was taken out from a vacuum glove box, and then spark plasma sintering was performed using a graphite mold at a sintering temperature of 550°C, a sintering pressure of 30 MPa, and a holding time of 20 min to obtain a porous graphene-reinforced aluminum-based composite material sample with a diameter of 30 mm and a thickness of about 20 mm.

[0061] (4) After the surface of the sintered aluminum-based composite material is polished smooth with sandpaper, hot extrusion is performed at 550° C. with an extrusion ratio of 25:1 to obtain a round rod-shaped aluminum material with a diameter of 6 mm, namely, a porous graphene-reinforced aluminum-based composite material.

[0062] The porous graphene reinforced aluminum-based composite material prepared in this example was processed by wire cutting into a sample that can be used for stretching, and a tensile test was carried out to test its room temperature tensile properties. The mechanical properties are shown in Table 1.

[0063] Comparative Example 1

[0064] The aluminum-based material is prepared in the same manner as in Example 2, except that no porous graphene reinforcement is added in this comparative example.

[0065] (1) Weigh 30g pure aluminum powder and 0.12g stearic acid (used as a process control agent to prevent large-area cold welding during ball milling) and place them in a stainless steel ball milling jar filled with argon. At a ball-to-material ratio of 20:1, use a planetary ball mill at 200 rpm for 8 hours.

[0066] (2) After the ball milling in step (1) is completed, high-speed ball milling is continued for 30 minutes at a ball milling speed of 450 rpm to achieve cold welding.

[0067] (3) The ball-milled mixed powder was taken out from a vacuum glove box, and then spark plasma sintering was performed using a graphite mold at a sintering temperature of 550°C, a sintering pressure of 50 MPa, and a holding time of 20 min to obtain an aluminum-based composite material sample with a diameter of 30 mm and a thickness of about 20 mm.

[0068] (4) After the surface of the sintered aluminum-based material is polished smooth with sandpaper, hot extrusion is performed at 550°C with an extrusion ratio of 25:1 to obtain a round rod-shaped aluminum material with a diameter of 6 mm.

[0069] The aluminum-based material prepared in this comparative example was processed into a sample that can be stretched by wire cutting, and a tensile test was performed to test its room temperature tensile properties. The results are as follows: Figure 4 The mechanical properties are shown in Table 1.

[0070] Comparative Example 2

[0071] This comparative example adopts the same method as Example 2 to prepare the aluminum-based composite material, except that: this comparative example uses reduced graphene oxide reinforcement phase instead of porous graphene reinforcement phase.

[0072] (1) Weigh 29.88 g pure aluminum powder and 0.12 g reduced graphene oxide powder (such as Figure 3As shown), 0.12g of stearic acid (used as a process control agent to prevent large-area cold welding during ball milling) were placed in a stainless steel ball milling jar and filled with argon. Under the condition of a ball-to-material ratio of 20:1, a planetary ball mill was used to firstly mill at 200 rpm for 8 hours to pre-disperse the reduced graphene oxide.

[0073] (2) After the ball milling in step (1) is completed, high-speed ball milling is continued for 30 minutes at a ball milling speed of 450 rpm to achieve cold welding.

[0074] (3) The ball-milled mixed powder was taken out from a vacuum glove box, and then spark plasma sintering was performed using a graphite mold at a sintering temperature of 550°C, a sintering pressure of 50 MPa, and a holding time of 20 min to obtain a reduced graphene oxide reinforced aluminum-based composite material sample with a diameter of 30 mm and a thickness of about 20 mm.

[0075] (4) After the surface of the sintered aluminum-based composite material is polished smooth with sandpaper, hot extrusion is performed at 550° C. with an extrusion ratio of 25:1 to obtain a round rod-shaped aluminum material with a diameter of 6 mm.

[0076] The aluminum-based composite material prepared in this comparative example was processed into a sample that can be stretched by wire cutting, and a tensile test was performed to test its room temperature tensile properties. The results are as follows: Figure 4 The mechanical properties are shown in Table 1.

[0077] Comparative Example 3

[0078] This comparative example adopts the same method as Example 3 to prepare a porous graphene reinforced aluminum-based composite material, except that: in this comparative example, the sintering pressure is reduced and a sintering pressure of 20 MPa is used for spark plasma sintering.

[0079] (1) Weigh 29.82 g of pure aluminum powder, 0.18 g of porous graphene powder, and 0.12 g of stearic acid (used as a process control agent to prevent large-area cold welding during ball milling) and place them in a stainless steel ball milling jar, which is then filled with argon. At a ball-to-material ratio of 20:1, a planetary ball mill is used to pre-disperse the porous graphene at 200 rpm for 7 hours.

[0080] (2) After the ball milling in step (1) is completed, high-speed ball milling is continued for 50 minutes at a ball milling speed of 450 rpm to achieve cold welding.

[0081] (3) The ball-milled mixed powder was taken out from a vacuum glove box, and then spark plasma sintering was performed using a graphite mold at a sintering temperature of 450°C, a sintering pressure of 20 MPa, and a holding time of 20 min to obtain a porous graphene-reinforced aluminum-based composite material sample with a diameter of 30 mm and a thickness of about 20 mm.

[0082] (4) After the surface of the sintered aluminum-based composite material is polished smooth with sandpaper, hot extrusion is performed at 550° C. with an extrusion ratio of 25:1 to obtain a round rod-shaped aluminum material with a diameter of 6 mm.

[0083] The aluminum-based composite material prepared in this comparative example was processed into a sample that can be stretched by wire cutting, and a tensile test was performed to test its room temperature tensile properties. The mechanical properties are shown in Table 1.

[0084] Comparative Example 4

[0085] In this comparative example, the porous graphene-reinforced aluminum-based composite material was prepared by the same method as in Example 4, except that in this comparative example, the ball milling time was extended, the pre-dispersion ball milling was 10 hours, and the high-speed ball milling was 70 minutes.

[0086] (1) Weigh 29.76 g of pure aluminum powder, 0.24 g of porous graphene powder, and 0.12 g of stearic acid (used as a process control agent to prevent large-area cold welding during ball milling) and place them in a stainless steel ball milling jar, which is then filled with argon. At a ball-to-material ratio of 20:1, a planetary ball mill is used to mill at 200 rpm for 10 hours to pre-disperse the porous graphene.

[0087] (2) After the ball milling in step (1) is completed, high-speed ball milling is continued for 70 minutes at a ball milling speed of 450 rpm to achieve cold welding.

[0088] (3) The ball-milled mixed powder was taken out from a vacuum glove box, and then spark plasma sintering was performed using a graphite mold at a sintering temperature of 550°C, a sintering pressure of 40 MPa, and a holding time of 20 min to obtain a porous graphene-reinforced aluminum-based composite material sample with a diameter of 30 mm and a thickness of about 20 mm.

[0089] (4) After the surface of the sintered aluminum-based composite material is polished smooth with sandpaper, hot extrusion is performed at 550° C. with an extrusion ratio of 14:1 to obtain a round rod-shaped aluminum material with a diameter of 8 mm.

[0090] The aluminum-based composite material prepared in this comparative example was processed into a sample that can be stretched by wire cutting, and a tensile test was performed to test its room temperature tensile properties. The mechanical properties are shown in Table 1.

[0091] Comparative Example 5

[0092] This comparative example adopts the same method as Example 5 to prepare a porous graphene reinforced aluminum-based composite material, except that: in this comparative example, the extrusion ratio is reduced, and the sintered block is hot extruded at an extrusion ratio of 4.6:1.

[0093] (1) Weigh 29.70 g of pure aluminum powder, 0.30 g of porous graphene powder, and 0.12 g of stearic acid (used as a process control agent to prevent large-area cold welding during ball milling) and place them in a stainless steel ball milling jar, which is then filled with argon. At a ball-to-material ratio of 20:1, a planetary ball mill is used to mill at 200 rpm for 7 hours to pre-disperse the porous graphene.

[0094] (2) After the ball milling in step (1) is completed, high-speed ball milling is continued for 40 minutes at a ball milling speed of 450 rpm to achieve cold welding.

[0095] (3) The ball-milled mixed powder was taken out from a vacuum glove box, and then spark plasma sintering was performed using a graphite mold at a sintering temperature of 550°C, a sintering pressure of 30 MPa, and a holding time of 20 min to obtain a porous graphene-reinforced aluminum-based composite material sample with a diameter of 30 mm and a thickness of about 20 mm.

[0096] (4) After the surface of the sintered aluminum-based composite material is polished smooth with sandpaper, hot extrusion is performed at 550° C. with an extrusion ratio of 4.6:1 to obtain a round rod-shaped aluminum material with a diameter of 10 mm.

[0097] The aluminum-based composite material prepared in this comparative example was processed into a sample that can be stretched by wire cutting, and a tensile test was performed to test its room temperature tensile properties. The mechanical properties are shown in Table 1.

[0098] Table 1

[0099] project Room temperature tensile strength (MPa) Room temperature elongation (%) Example 1 358.48 17.57 Example 2 425.45 18.25 Example 3 394.78 17.64 Example 4 376.34 17.23 Example 5 328.12 16.89 Comparative Example 1 284.08 22.87 Comparative Example 2 307.89 16.23 Comparative Example 3 325.66 17.02 Comparative Example 4 317.18 16.89 Comparative Example 5 268.35 16.13

[0100] It can be seen from Table 1 that, compared with Comparative Example 1, the room temperature elongation of Examples 1-5 and Comparative Example 2 is decreased to a certain extent, indicating that the composite material prepared by the composite of graphene and aluminum-based matrix inevitably produces hard-brittle phase Al4C3, resulting in a decrease in the elongation of the composite material relative to the aluminum-based material. However, compared with Comparative Example 2, the room temperature elongation of Examples 1-5 is relatively high, and the degree of decrease in the room temperature elongation of Examples 1-5 relative to Comparative Example 1 is relatively low, indicating that the porous graphene reinforced aluminum-based composite material prepared by the present invention can effectively compensate for the negative impact of the hard-brittle phase Al4C3 on the elongation of the composite material, weaken the negative impact of the hard-brittle phase Al4C3 on the elongation of the composite material, and improve the comprehensive mechanical properties of the composite material.

[0101] By comparing Example 2 with Comparative Example 1, it can be seen that the tensile strength of the pure aluminum matrix without adding a reinforcement is greatly improved by adding porous graphene, the elongation at room temperature is slightly reduced, and the comprehensive mechanical properties of the composite material are improved.

[0102] By comparing Example 2 and Comparative Example 2, it can be seen that by using porous graphene as a reinforcing phase, the strength of the composite material is significantly improved, and the room temperature elongation is also improved to a certain extent. This is because the porous graphene reacts with the aluminum matrix to provide more contact points, enhance interface bonding, reduce crack propagation, and further improve the comprehensive mechanical properties of the composite material.

[0103] By comparing Example 3 with Comparative Example 3 and Example 5 with Comparative Example 5, it can be seen that with the increase of sintering pressure and extrusion ratio, the tensile strength of the composite material is improved. This is because the pores in the material are eliminated, and the uniform and dense structure can better transfer and disperse stress. In addition, the grain size of the aluminum matrix is ​​continuously refined, the porous graphene is more evenly dispersed, and the interface bonding is better. The porous graphene can more fully exert the reinforcement effect, thereby significantly improving the mechanical properties of the composite material at room temperature.

[0104] By comparing Example 4 with Comparative Example 4, the ball milling time of Comparative Example 4 is longer, but its tensile strength is lower than that of Example 4. This is because the increase in ball milling time destroys the structure of graphene, such as shearing or tearing. Long-term ball milling causes the graphene sheets to re-agglomerate and form larger aggregates, resulting in a decrease in its performance.

[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a porous graphene reinforced aluminum-based composite material, characterized in that: The preparation method comprises the following steps: (1) Pre-dispersion ball milling: Under argon protection, the mixed powder of porous graphene powder and Al powder is pre-dispersed and ball milled; (2) ball milling: under argon protection, the mixed powder after pre-dispersion and ball milling in step (1) is subjected to high-speed ball milling to achieve cold welding and obtain cold welding powder; (3) Sintering: spark plasma sintering the cold welding powder obtained in step (2) to obtain a sintered block; (4) hot extruding the sintered block obtained in step (3), and obtaining a porous graphene-reinforced aluminum-based composite material after cooling.

2. The preparation method according to claim 1, characterized in that: In the step (1), the mass of the porous graphene powder accounts for 0.2% to 1% of the total mass of the mixed powder, and the remainder is Al powder.

3. The preparation method according to claim 1, characterized in that: In the step (1), the ball-to-material ratio is 20:1, the ball milling speed is 200 rpm, and the ball milling time is 6 to 8 hours.

4. The preparation method according to claim 1 or 3, characterized in that: In the step (1), 0.4% of the total mass of the mixed powder is added as a processing control agent during ball milling.

5. The preparation method according to claim 1, characterized in that: In the step (2), the ball-to-material ratio is 20:1, the ball milling speed is 450 rpm, and the ball milling time is 30 to 60 min.

6. The preparation method according to claim 1, characterized in that: In the step (3), the sintering vacuum degree is less than 10Pa, the sintering temperature is 450°C to 550°C, the temperature is kept for 20 minutes, and the sintering pressure is 30 to 50MPa.

7. The preparation method according to claim 1, characterized in that: In the step (4), the extrusion temperature is 550° C. and the extrusion ratio is 9:1 to 25:

1.

8. A porous graphene reinforced aluminum-based composite material, characterized in that: The composite material is prepared by the preparation method according to any one of claims 1, 2, 3, 5, 6 and 7.

Citation Information

Patent Citations

  • Preparation method of graphene-based nanocomposite material having three-dimensional porous structure

    CN104003374A

  • Preparation method of graphene-reinforced copper-based composite

    CN105624445A

  • Single-layer graphene / aluminum composite material and preparation method thereof

    CN107675028A

  • Graphene / aluminum composite conductive material and preparation method thereof

    CN109686501A

  • Powder metallurgy preparation method of graphene reinforced aluminum-based composite material

    CN112725660A